The New View of Investment: A Neoclassical Analysis - Phelps, Edmund S. (Quarterly Journal of Economics, 1962)
The basis of investment pessimism, 549. — The new view, 551. — A simple model of growth, 553. — Investment and productivity in the long run, 555. — Investment and productivity in the short run, 560. — The rate of return on current investment, 563.— Summary, 567.